The Relationship Between the Duration of Hemodialysis Therapy and the Level of Adherence to Fluid Restriction Among Patients with Chronic Kidney Failure at Pasar Rebo Hospital - Muhammad Naufal Fikri (PT Publikasiku Academic Solution, 2026)
Chronic Kidney Disease (CKD) is a progressive and irreversible condition that requires long-term renal replacement therapy, particularly hemodialysis. Adherence to fluid restriction is a critical component in preventing complications such as hypertension, pulmonary edema, and cardiovascular disorders among patients undergoing hemodialysis. One factor that may influence adherence is the duration of hemodialysis therapy. This study, “The Relationship Between the Duration of Hemodialysis Therapy and the Level of Adherence to Fluid Restriction Among Patients With Chronic Kidney Failure at Pasar Rebo Hospital”, aimed to examine the relationship between the duration of hemodialysis therapy and the level of adherence to fluid restriction among patients with chronic kidney failure at Pasar Rebo Hospital. This study employed a quantitative analytical observational design with a cross-sectional approach. A total of 42 patients undergoing hemodialysis at Pasar Rebo Hospital were selected as respondents. Data on the duration of hemodialysis therapy were obtained from medical records, while adherence to fluid restriction was measured using a modified questionnaire adapted from Amanu (2020). Univariate analysis was used to describe respondent characteristics and variable distributions, while bivariate analysis was conducted using the Pearson Chi-Square test to determine the relationship between variables. The findings showed that most respondents had undergone hemodialysis therapy for >=25 months (57.1%). Regarding adherence, 50.0% of respondents were categorized as adherent, 38.1% as moderately adherent, and 11.9% as non-adherent. Crosstabulation analysis indicated that patients with longer therapy durations demonstrated higher adherence levels. Statistical testing revealed a significant relationship between the duration of hemodialysis therapy and fluid restriction adherence (p = 0.006). Overall, there is a significant relationship between the duration of hemodialysis therapy and adherence to fluid restriction among patients with chronic kidney failure. Longer exposure to hemodialysis therapy is associated with improved adherence behavior, highlighting the importance of continuous patient education and support, particularly for individuals in the early stages of hemodialysis treatment.